FORMULATION AND EVALUATION OF FLOATING-MUCOADHESIVE MICROSPHERES OF NOVEL NATURAL POLYSACCHARIDE FOR SITE SPECIFIC DELIVERY OF RANITIDINE HYDROCHLORIDE - Sahu, Vikram Kumar; Sharma, Nitin; Sahu, Pratap Kumar; Saraf, Shubhini A. (International Journal of Applied Pharmaceutics, 2017)
Objective: Localization of ranitidine hydrochloride (RH) into the upper part of the intestinal tract is beneficial for better drug bioavailability. Present work described the method of preparation of novel plant polysaccharide based floating microspheres for delivery of the drug into the stomach. Methods: Polysaccharide was extracted from the seeds of plant Tamarindus indica (TI). Extracted polysaccharide was evaluated for some physicochemical parameters. Floating-mucoadhesive microspheres were prepared by using extracted polysaccharide as mucoadhesive excipients while eudragit as a release controlling polymers by using emulsion crosslinking method. Chemical crosslinking was done by using epichlorohydrin. Prepared microspheres were evaluated for their drug-polymer compatibility study by using fourier transform infrared spectroscopy (FT-IR). Further characterization such as size, surface properties, swelling index, percentage encapsulation, in vitro buoyancy and drug release was performed. Results: FT-IR study confirms the chemical crosslinking of extracted polysaccharide and also drug stability during processing of microspheres. The size of microspheres was in the range of 5.38 to 7.84 Âµm. SEM images revealed that all batches were of spherical in size and smooth surface. The swelling index showed better swelling in the range of 158-257 percentages. Encapsulation efficiency was found to be decreased by decreasing the concentration of polysaccharide. In vitro buoyancy study possesses that formulation F1 showed better floating ability as compared to the others. Finally, in vitro drug release study revealed that prepared microspheres were able to release the 100% drug within 8-12 h, indicating sustain release behavior. Conclusion: Present study concludes that polysaccharide of TI may be used as excipients for the preparation of floating-mucoadhesive microspheres.